Pengaruh Edukasi Dash Diet terhadap Tingkat Pengetahuan dan Kepatuhan Kontrol Tekanan Darah pada Lansia Hipertensi - Nurul Imam; Nurmawati S Lataima; Shinta Wurdiana Rhomadona; Khalifatus Zuhriyah Alfianti (Pusat riset dan Inovasi Nasional, 2025)
Hypertension is a common health problem in the elderly that is often unrealized, so it requires effective education to improve blood pressure management. This study aims to determine the effect of DASH diet education on knowledge and compliance with blood pressure control in hypertensive elderly at the Surabaya Elderly Posyandu. A quasi-experimental method with a pretest-posttest design and a control group involved 40 elderly hypertensive respondents who were divided into intervention and control groups. The intervention group received DASH diet education through counseling, leaflets, and 1x/week discussions for 4 weeks. Results showed a significant improvement in p=0.000 knowledge and p=0.000 blood pressure control adherence in the intervention group, while the control group showed no significant change. Systolic and diastolic blood pressure in the intervention group also decreased significantly (158.2/94.3 to 139.7/84.5 mmHg), with 55% of respondents achieving normal blood pressure, compared to 10% in the control group. Conclusion: DASH diet education is effective in improving knowledge, compliance, and controlling blood pressure in hypertensive elderly. Similar educational programs are recommended to be implemented continuously in primary health services for more optimal hypertension management.